Características de prescripción-indicación de los antimicrobianos de reserva en el servicio de neonatología del Hospital Regional Docente de Trujillo, agosto 2011 - agosto 2012 - Silva Rojas, David (2014)
This research is a descriptive and retrospective study of the characteristics of prescription and indication of reserve antimicrobials at the Neonatology Service of Hospital Regional Docente de Trujillo, August 2011- August 2012, that takes as a study sample all prescriptions done by the pharmacy department through its format for prescription of reserve antimicrobials at the Neonatology Service of the Hospital Regional Docente de Trujillo. In this study shows that indication-prescription of antimicrobial reserve are suitably used in a percentage higher than 90%, mainly cefotaxime cefatazidima, vancomycin and imipenem. In the study by prescription-indication, it was found that antimicrobials are used appropriately in a percentage higher than 90%, in diseases such pneumonia, neonatal sepsis and septic shock. We conclude that in the Neonatology Service, doctors are using the indication-prescription in a proper way